Answer:
Part a) 0.63
Part b) 0.22
Part c) 0.68
Step-by-step explanation:
The individual probabilities are calculated as
1) Probability of scoring in first attempt = 70%
2) Probability of missing in first attempt = 30%
3) Probability of scoring in second attempt provided she scores in first attempt = 90%
4) Probability of missing in second attempt provided she scores in first attempt = 10%
5) Probability of scoring in 2nd attempt provided she misses in ist attempt = 50%
6) Probability of missing in 2nd attempt provided she misses in ist attempt = 50%
Part a)
probability of making the throw exactly both the times = [tex]P(ist)\times P (2nd)[/tex]
Applying values we get
probability of making the throw exactly both the times= [tex]0.7\times 0.9=0.63[/tex]
Part b)
She will make it exactly once if
1) She scores in first attempt and misses second
2) She misses in first attempt and scores in the second attempt
Probability of case 1 = [tex]0.7\times 0.1=0.07[/tex]
Probability of case 2 =[tex] 0.3 \times 0.5 =0.15[/tex]
Thus probability She will make it exactly once equals [tex] 0.15+0.07=0.22[/tex]
Part c)
It is a case of conditional probability
Now by Bayes theorem we have
[tex]P(B|A)=\frac{P(B\cap A)}{P(A)}[/tex]
P(B|A) is the probability of scoring in second attempt provided that she has scored only once
P(B) is the probability of scoring exactly once
Given that she makes it exactly once [tex]\therefore P(A)=0.22[/tex]
[tex]P(B\cap A)=0.15[/tex]
using these values we have
[tex]P(B|A)=\frac{0.15}{0.22}\\\\P(B|A)=0.68[/tex]
the vertex of this parabola is at (5,5). when the x-value is 6, the y-value is -1. what is the coefficient of the squared in the parabola's equations
Answer: OPTION D.
Step-by-step explanation:
The vertex form of a quadratic function is:
[tex]y= a(x - h)^2 + k[/tex]
Where (h, k) is the vertex of the parabola and "a" is the coefficient of the squared in the parabola's equation.
We know that the vertex of this parabola is at (5,5) and we also know that when the x-value is 6, the y-value is -1.
Then we can substitute values into [tex]f (x) = a(x - h)^2 + k[/tex] and solve for "a". This is:
[tex]-1= a(6- 5)^2 + 5\\\\-1=a+5\\\\-1-5=a\\\\a=-6[/tex]
Answer:
D
Step-by-step explanation:
HELPPPP!!!!!!!!!!!!!!!! (10 points) We want to know the probability that a student selected randomly from her class would have an “A” (90 or above) in her class. Find the probability. Explain HOW to find the probability
Answer:
23 out of 91
around 1/3 of the class
Step-by-step explanation:
the total number of students so around the third part of the class
Can you use the Law of Cosines in the triangle below? Why or why not?
Answer:
Yes
Step-by-step explanation:
The law of cosines relates the three sides of a triangle with the cosine of the angle opposite one of them. It is useful for finding an angle of the triangle when only the side lengths are given, as here.
The cost in dollars to manufacture x pairs of shoes is given by 12,000 + 19x. This month, the manufacturer produced 1000 more pairs of shoes than last month. The average cost per pair dropped by $0.43.
a) Write an expression for the average cost per pair of shoes. Use this expression to write an equation to represent there situation.
b) Solve your equation
c) Are there any mathematical restrictions on the domain? Explain.
d) Determine reasonable domain in the context of the problem. Use your answers to parts I and II to answer the question.
Answer:
(a) The expression for the average cost per pair of shoes is [tex]A(x)=\frac{12000}{x}+19[/tex] and equation for the situation is [tex]\frac{12000}{x}+19-(\frac{12000}{x+1000}+19)=0.43[/tex].
(b) x=[tex]x\approx 4806[/tex]
(c) The average function is not defined for x=0, so the domain of the function is all real numbers except 0.
(d) The reasonable domain is all natural numbers.
Step-by-step explanation:
The cost in dollars to manufacture x pairs of shoes is given by
[tex]C(x)=12000+19x[/tex]
where, x is the pairs of shoes.
(a)
The expression for the average cost per pair of shoes.
[tex]A(x)=\frac{C(x)}{x}[/tex]
[tex]A(x)=\frac{12000+19x}{x}[/tex]
[tex]A(x)=\frac{12000}{x}+19[/tex]
This month, the manufacturer produced 1000 more pairs of shoes than last month. The average cost per pair dropped by $0.43.
[tex]A(x)-A(x+1000)=0.43[/tex]
[tex]\frac{12000}{x}+19-(\frac{12000}{x+1000}+19)=0.43[/tex]
Therefore the expression for the average cost per pair of shoes is [tex]A(x)=\frac{12000}{x}+19[/tex] and equation for the situation is [tex]\frac{12000}{x}+19-(\frac{12000}{x+1000}+19)=0.43[/tex].
(b)
On solving the above equation we get
[tex]\frac{12000}{x}-\frac{12000}{x+1000}=0.43[/tex]
[tex]\frac{12000000}{x^2 + 1000 x} = 0.43[/tex]
[tex]12000000=0.43(x^2 + 1000 x)[/tex]
[tex]12000000=0.43x^2 + 430x[/tex]
[tex]0=0.43x^2 + 430x-12000000[/tex]
Using graphing calculator we get
[tex]x\approx -5806.31,4806.31[/tex]
The pair of shoe can not be native and decimal value.
[tex]x\approx 4806[/tex]
Therefore the solution is [tex]x\approx 4806[/tex].
(c)
The average cost function is
[tex]A(x)=\frac{12000}{x}+19[/tex]
The function is not defined if the denominator is 0.
The above function is not defined for x=0, so the domain of the function is all real numbers except 0.
(d)
In the average function x represents the number of pair of shoe.
It means the value of x must be a positive integer.
Since the average function is not defined for x=0, So the reasonable domain of average function is
Domain={x : x∈Z⁺, x≠0}
Domain=N
Therefore the reasonable domain is all natural numbers.
Does the point “is on the circle shown? Explain.
Answer:
Option 2: Yes, the distance from (-2,0) to (1,√7) is 4 units
Step-by-step explanation:
The point is:
(1,√7)
If the point lies on the circle, then the distance of point and the center of circle should be equal to the radius of the circle.
The radius can be viewed from the diagram that it is 4 units.
The center is: (-2,0)
Now, distance:
[tex]d = \sqrt{(x_2-x_1)^{2}+ (y_2-y_1)^{2}}\\ d = \sqrt{(-2-1)^{2}+ (0-\sqrt{7} )^{2}}\\ d = \sqrt{(-3)^{2}+ (-\sqrt{7} )^{2}}\\=\sqrt{9+7}\\ =\sqrt{16}\\ =4[/tex]
Hence, option 2 is correct ..
The value of a collector’s item is expected to increase exponentially each year. The item is purchased for $500. After 2 years, the item is worth $551.25. Which equation represents y, the value of the item after x years?y = 500(0.05)xy = 500(1.05)xy = 500(0.1025)xy = 500(1.1025)x
Answer:
y = 500(1.05)^x.
Step-by-step explanation:
551.25 = 500x^2 where x is the multiplier for each year.
x^2 = 551.25/500
x = 1.05
So the value after x years is 500(1.05)^x.
Answer: [tex]y=500(1.05)^x[/tex]
Step-by-step explanation:
The exponential growth equation is given by :-
[tex]y=A(1+r)^x[/tex] (1)
, where A is the initial value of , r is the rate of growth ( in decimal) and t is the time period ( in years).
Given : The value of a collector’s item is expected to increase exponentially each year.
The item is purchased for $500. After 2 years, the item is worth $551.25.
Put A= 500 ; t= 2 and y= 551.25 in (1), we get
[tex]551.25=500(1+r)^2\\\\\Rightarrow\ (1+r)^2=\dfrac{551.25}{500}\\\\\Rightarrow (1+r)^2=1.1025[/tex]
Taking square root on both sides , we get
[tex]1+r=\sqrt{1.1025}=1.05\\\\\Rightarrow\ r=1.05-1=0.5[/tex]
Now, put A= 500 and r= 0.5 in (1), we get the equation represents y, the value of the item after x years as :
[tex]y=500(1+0.5)^x\\\\\Rightarrow\ y=500(1.05)^x[/tex]
What is this (pic provided) written as a single log?
Answer:
Step-by-step explanation:
when logs are added, they can be multiplied to produce a simplified log.
log_5(4*7) + log_5(2)
log_5(4*7*2)
log_5(56)
If you were to place $2500 in a savings account that pays 3% interest compound continually how much money will you have after 5 years. Assume you make no other deposits or withdrawals.
[tex]\bf ~~~~~~ \textit{Continuously Compounding Interest Earned Amount} \\\\ A=Pe^{rt}\qquad \begin{cases} A=\textit{accumulated amount}\\ P=\textit{original amount deposited}\dotfill & \$2500\\ r=rate\to 3\%\to \frac{3}{100}\dotfill &0.03\\ t=years\dotfill &5 \end{cases} \\\\\\ A=2500e^{0.03\cdot 5}\implies A=2500e^{0.15}\implies A\approx 2904.59[/tex]
Answer:
C. $2904.59
Step-by-step explanation:
Compounded continually means that the principal amount is constantly earning interest and the interest keeps earning on the interest earned.
The formula to apply is
[tex]A=Pe^{rt}[/tex]
where A is the amount, P is the principal, r is rate of interest, t is time in years and e is the mathematical constant
Taking
e=2.7183, P=$2500, r=3% and t=5 years
[tex]A=Pe^{rt} \\\\\\A=2500*2.7183^{0.03*5} \\\\\\A=2500*1.1618\\\\\\A=2904.59\\\\A=2904.59[/tex]
Safari Adventure Theme Park is a selfguided theme park in which people drive through a park filled with African wildlife. They are given a map and a written guide to the wildlife of the park. They charge $20.00 per car plus $2.00 per person in the car. The number of people per car can be represented by the random variable X which has a mean value μX = 3.2, and a variance σ2x = 1.4. What is the mean of the total amount of money per car that is collected entering the park?
Answer:
$26.40
Step-by-step explanation:
For a linear function, the mean of the function is the function of the mean:
20 + 2.00·μX = 20 + 2.00·3.2 = 20 + 6.40 = 26.40 . . . . dollars
The mean total amount collected per car entering the Safari Adventure Theme Park is $26.40.
The mean of the total amount of money collected per car entering the park can be calculated by finding the expected value of the total amount, considering the price per car and per person. In this case, the mean total amount collected per car = price per car + (mean number of people per car) * price per person. Substituting the given values: 20 + 3.2 * 2 = $26.40.
A pair of angles which share a common side and vertex is called
Answer: Adjacent Angles
A pair of angles which share a common side and vertex is called adjacent angles.
What is an angle measure?When two lines or rays intersect at a single point, an angle is created. The vertex is the term for the shared point. An angle measure in geometry is the length of the angle created by two rays or arms meeting at a common vertex.
Given:
A pair of angles which share a common side and vertex.
If two angles share a side and a vertex, they are said to be adjacent in geometry.
In other words, adjacent angles do not overlap and are placed precisely next to one another.
Therefore, the right definition is adjacent angles.
To learn more about the angle measure;
brainly.com/question/14684647
#SPJ6
If f(x) = 2x + 2 and g(x) = x3, what is (gºf)(2)?
Answer:
216
Step-by-step explanation:
(g∘f)(x) = g(f(x))
f(2) = 2·2 +2 = 6
g(f(2)) = g(6) = 6³ = 216
Answer:
216
Step-by-step explanation:
Correct Plato
What is the third term in the binomial expansion of (3x+y^3)^4
Answer:
The last choice is the one you want.
Step-by-step explanation:
Use the 5th row of Pascal's Triangle. Since you have a 4th degree polynomial, there will be 5 terms in it. The 5 coefficients, in order, are:
1, 4, 6, 4, 1
We will use these coefficients only up to and including the third one, since that is the one you want. Binomial expansion using Pascal's Triangle looks like this:
[tex]1(3x)^4(y^3)^0+4(3x)^3(y^3)^1+6(3x)^2(y^3)^2+...[/tex]
That third term is the one we are interested in. That simplification gives us:
[tex]6(9x^2)(y^6)[/tex]
Multiply 6 and 9 to get 54, and a final term of:
[tex]54x^2y^6[/tex]
The third term of the given binomial expansion is [tex]54(x^{2})(y^{5})\\[/tex]
What is binomial expansion?The binomial expansion is based on a theorem that specifies the expansion of any power [tex](a+b)^{m}[/tex] of a binomial (a + b) as a certain sum of products [tex]a^{i} b^{i}[/tex], such as (a + b)² = a² + 2ab + b².
How to find the third term in the binomial expansion of (3x+y^3)^4 ?We know that the binomial expansion of [tex](a+b)^{m}[/tex] can be written as [tex]mC_{0}(a^{m-0}) +mC_{1}(a^{m-1})b+ mC_{2}(a^{m-2})b^{2}+..................+mC_{m}b^{m}[/tex]So the (r+1)th term will be [tex]mC_{r}(a^{m-r})b^{r}[/tex]The given term is [tex](3x + y^{3}) ^{4}[/tex]
The third term in the expansion will be
[tex]4C_{2}(9x^{2})(y^{3})^{2}\\ = 54(x^{2})(y^{5})\\[/tex]
Find more about "Binomial Expansion" here : https://brainly.com/question/13602562
#SPJ2
A new board game comes with a deck of 20 cards: 5 red, 3 blue, 2 orange, and 10 green.
After the deck is shuffled, the player is to choose the top card and note its color, replace
the card, shuffle the deck again, and then choose the top card again and note its color.
What is the probability that both cards selected are blue?
Can someone let me know if I simplified these equations correctly or at least show me how to do it?
Answer:
Your work is correct as far as it goes. Now eliminate the terms that are zero.
Step-by-step explanation:
Multiplying anything by zero gives zero. Adding zero is like adding nothing. Zero is called the "additive identity element" because ...
a + 0 = a
Adding zero doesn't change anything. You can (and should) drop the zero if your goal is to simplify the expression.
[tex]a. \quad x_{f}=v_{0}\\\\b. \quad x_{f}=v_{0}t\\\\c. \quad v_{f}^2=v_{0}^2[/tex]
Determine whether the two triangles are similar. HELP ASAP! I AM RUNNING OUT OF POINTS!!
Answer:
ΔKLJ ~ ΔRPQ by AA~
Step-by-step explanation:
Angle angle similarity needs two corresponding angles in two triangles to be same. The two given triangles are similar by: ΔKLJ ~ ΔRPQ by AA~
How to find measure of missing third angle in a triangle?It is a theorem in mathematics that sum of internal angles of a triangle equate to [tex]180^\circ[/tex]
Suppose that two angles are given as [tex]a^\circ[/tex] and [tex]b^\circ[/tex] and let there is one angle missing. Let its measure be [tex]x^\circ[/tex]
Then, by the aforesaid theorem, we get:
[tex]a^\circ + b^\circ + x^\circ = 180^\circ\\\\ \text{Subtracting a + b degrees from both sides} \\\\x^\circ = 180^\circ - (a^\circ + b^\circ)[/tex]
What is Angle-Angle similarity for two triangles?Two triangles are similar if two corresponding angles of them are of same measure. It is because when two pairs of angles are similar, then as the third angle is fixed if two angles are fixed, thus, third angle pair also gets proved to be of same measure. This makes all three angles same and thus, those two triangles are scaled copies of each other. Thus, they're called similar.
For given case, we've got
[tex]m\angle K = m\angle R\\m\angle J = m\angle Q\\[/tex]
Thus, for the rest of the angle pair, we have:
[tex]m\angle L = 180 - (m\angle J + m\angle K) = 180 - (m\angle Q + m\angle R) = m\angle P\\\\m\angle L = m\angle P[/tex]
Thus, given two triangles are similar by angle-angle similarity.
Thus,
The two given triangles are similar by: ΔKLJ ~ ΔRPQ by AA~
Learn more about angle-angle similarity here:
https://brainly.com/question/11929676
What ia the measure of x?
Answer:
58
Step-by-step explanation:
Rule: the exterior angle = the sum of the two angles that do not share a side with the exterior angle. Put in much simpler terms <DAB = <B + <C
Solution
<C + <B = <DAB
<C + 56 = 114 Subtract 56 from both sides
<C +56-56 = 114-56 Combine
<C = 58
x = 58
Evaluate the expression
5⋅x3x2\dfrac{5\cdot x^3}{x^2}
x
2
5⋅x
3
start fraction, 5, dot, x, start superscript, 3, end superscript, divided by, x, start superscript, 2, end superscript, end fraction
for
x=2x=2
x=2
x, equals, 2
The simplified expression for [tex]\((5 \cdot x^3) / (x^2)\) is \(5 \cdot x\).[/tex]
When x = 2, the result is [tex]\(5 \times 2 = 10.[/tex]
The answer is 10.
To evaluate the expression[tex]\((5 \cdot x^3) / (x^2)\) for \(x = 2\),[/tex] we first need to simplify the given expression.
Given:
[tex]\[ \dfrac{5 \cdot x^3}{x^2} \][/tex]
Simplifying, we divide the powers of x :
[tex]\[ x^3 / x^2 = x^{3-2} = x^1 = x. \][/tex]
So the expression simplifies to:
[tex]\[ 5 \cdot x. \][/tex]
Now substitute x = 2 :
[tex]\[ 5 \cdot 2 = 10[/tex]
Thus, the value of [tex]\((5 \cdot x^3) / (x^2)\) when \(x = 2\)[/tex] is: 10.
Question : Evaluate the expression [tex]\[ \dfrac{5 \cdot x^3}{x^2} \][/tex]for x = 2. start fraction, 5, dot, x, cubed, divided by, x, squared, end fraction for x=2x=2x, equals, 2.
Proportions in Triangles (3)
Answer:
7 6/7
Step-by-step explanation:
Parallel segment BD creates triangle BDC similar to triangle AEC. The sides and segments of similar triangles are proportional:
x/11 = 5/7
x = 55/7 = 7 6/7 . . . . . multiply by 11
Name an intersection of plane GFL and plane that contains points A and C
The intersection of plane GFL and a plane that contains points A and C can be any plane that passes through those two points.
In mathematics, an intersection of two planes is the set of points that are common to both planes.
In this case, we want to find the intersection of plane GFL and a plane that contains points A and C.
Since both points A and C lie on the same plane, any plane that contains both points A and C would intersect plane GFL at those points.
Therefore, any plane that passes through points A and C would be an intersection of plane GFL and a plane that contains points A and C.
Examples of planes that contain points A and C are:
A plane that contains the line segment AC
A plane that is perpendicular to line AC at point A
A plane that is perpendicular to line AC at point C
For more such questions on intersection of plane, click on:
https://brainly.com/question/118569
#SPJ12
[tex]cos\frac{x}{2} =[/tex]±[tex]\sqrt{\frac{1+cosx}{2} }[/tex], if A=[tex]\frac{x}{2}[/tex] then cosA=
Answer:
[tex]\cos{A}=\pm\sqrt{\dfrac{1+\cos{x}}{2}}[/tex]
Step-by-step explanation:
[tex]\cos{A}=\cos{\frac{x}{2}}=\pm\sqrt{\dfrac{1+\cos{x}}{2}}[/tex]
Apparently, you're supposed to recognize that the formula tells you the value of cos(x/2).
Find the product. 8y 3(-3y 2)
For this case we must find the product of the following expression:
[tex]8y ^ 3 (-3y ^ 2) =[/tex]
We have to by law of signs of multiplication:
[tex]+ * - = -[/tex]
Also, by definition of multiplication of powers of the same base, we put the same base and add the exponents, then the expression is rewritten as:
[tex]-24y ^ {3 + 2} =\\-24y ^ 5[/tex]
Answer:
[tex]-24y ^ 5[/tex]
Answer:
The Answer is -24y^5
Step-by-step explanation:
We know this because multiplying 8 by -3 = -24
Then we have to combine the exponents and we get 5.
Hope I helped. I used a website called mathwa3 to help, the 3 stands for a y.
Have a great day!!!
Evaluate 3x3 − 2x2 for x = -2.
Step-by-step explanation:
3x3-2x2
3(-2)3-2(-2)2
-6×3+4×2
-18+8
-10
I hope it will help you!
Answer:
-10
Step-by-step explanation:
Yes. All you have to remember is that double negatives result in POSITIVES.
I am joyous to assist you anytime.
Choose the correct absolute value inequality and graph for the solution -1.2≤x≤2
options:
|5x-2|>=8
|5x-2|<=8
Answer:
[tex]\large\boxed{|5x-2|\leq8}[/tex]
Step-by-step explanation:
[tex]-1.2\leq x\leq2\qquad\text{multiply all sides by 5}\\\\-6\leq5x\leq10\qquad\text{subtract 2 from both sides}\\\\-8\leq5x-2\leq8\iff|5x-2|\leq8[/tex]
If f(x) = 2x - 3 and g(x) = Radical over x-8,
what is (fºg)(24)?
Answer:
5
Step-by-step explanation:
Plug in 24 for x in your g(x) equation.
[tex]g(24)=\sqrt{24-8} \\g(24)=\sqrt{16} \\g(24)=4[/tex]
Next, plug in your g(x) value, 4, to your f(x) equation for x.
[tex]f(4)=2(4)-3\\f(4)=8-3\\f(4)=5[/tex]
What is the degree of vertex B?
Answer:
2
Step-by-step explanation:
The degree of the vertex B is 2 because from vertex B there are 2 line segments coming out of it.
Another example, C has degree 4 because from it there are 4 line segments coming from it.
Y – 4 = 20 A. The difference between a number and 4 is 20. B. The product of a number and 4 is 20. C. A number combined with 4 is 20. D. The quotient of a number and 4 is 20.
Answer:
A
Step-by-step explanation:
Subtraction means "difference". The only choice there that has the word "difference" in it is choice A.
Emails arrive at the server of a company at the rate of an average of 10 per hour. It is assumed that a Poisson process is a good model for the arrivals of the emails. What is the probability (to 2 decimal places) that the time between two consecutive emails is more than two minutes?
Answer:
0.37
Step-by-step explanation:
we have given that emails arrives at the server at the rate of 10 per hour means [tex]\frac{10}{60}=0.166[/tex] per minute
we have to find the probability that the time difference between the two email is more than 2 minute
so probability [tex]P\left ( X> 2 \right )=e^{-2\lambda }=e^{-2\times 0.166}=0.7166[/tex]
The probability that the time between two consecutive emails arriving at the server is more than two minutes is 0.72 (or 72%).
Given:
- Average rate of email arrivals [tex](\( \lambda \))[/tex] = 10 per hour
1. Understanding the Poisson Process:
- In a Poisson process, the time between events (in this case, email arrivals) follows an exponential distribution.
- If [tex]\( \lambda \)[/tex] is the average rate of events per unit time (here, per hour), the time between events (interarrival time) T follows an exponential distribution with parameter [tex]\( \lambda \)[/tex].
2. Parameter Conversion:
- Since [tex]\( \lambda = 10 \)[/tex] emails per hour, we convert this to the rate per minute:
[tex]\[ \lambda_{\text{minute}} = \frac{10}{60} = \frac{1}{6} \text{ emails per minute} \][/tex]
3. Probability Calculation:
- We are interested in the probability that the time between two consecutive emails is more than two minutes.
- Let X denote the time between two consecutive emails. X follows an exponential distribution with rate [tex]\( \lambda_{\text{minute}} = \frac{1}{6} \)[/tex].
[tex]\[ P(X > 2) = e^{-\lambda_{\text{minute}} \cdot 2} \][/tex]
Substitute [tex]\( \lambda_{\text{minute}} = \frac{1}{6} \)[/tex]:
[tex]\[ P(X > 2) = e^{-\frac{1}{6} \cdot 2} \] \[ P(X > 2) = e^{-\frac{1}{3}} \][/tex]
4. Calculating the Probability:
- Use a calculator to find [tex]\( e^{-\frac{1}{3}} \)[/tex].
[tex]\[ e^{-\frac{1}{3}} \approx 0.7165 \][/tex]
Therefore, the probability that the time between two consecutive emails is more than two minutes is approximately 0.72 (rounded to two decimal places).
This result aligns with the characteristics of a Poisson process with an average arrival rate of 10 emails per hour.
Apple trees cost $ 30 each, and cherry trees cost $ 40 each. Rohan has $ 600 to spend on fruit trees.
a) Let x represent the number of apple trees purchased, and let y represent the number of cherry trees purchased.
b) Write an equation that illustrates the different ways Rohan can purchase apple trees and cherry trees and spend exactly $ 600 .
Equation:
Answer:
A) Apples: $30x
Cherry: $40y
B) ($30x)+($40y)=600
In the coin value formula, V(t)= P(1+r)^t, which parts form the base of the exponential function? Which parts from the constant, or initial value? Which parts form the exponent?
Answer:
Step-by-step explanation:
The base of the exponential function is 1 + r.
The initial value is P.
The exponent is t.
The base of the exponential function is 1 + r
exponent is t, and
initial value is P
What is exponential function?The mathematical expression for an exponential function is f (x) = a ˣ, where “x” denotes a variable and “a” denotes a constant. This constant is referred to as the base of the function and should be greater than zero. The most common use exponential function is with base e
Given A coin formula V(t) = P(1+r)^t
to find the initial value put t = 0
V(0) = P(1+r)⁰
V(0) = P
P is the initial value
and exponent is the term which is in the power of any exponential function
here t is exponent and (1+r) is base function
Hence according to coin formula The base of the exponential function is 1 + r; exponent is t; and initial value is P.
Learn more about exponential function
https://brainly.com/question/14355665
#SPJ5
Please help me!
The angle of elevation of the top of a tower to a point on the ground is 61°. At a point 600 feet farther from the base, in line with the base and the first point and in the same plane, the angle of elevation is 32°. Find the height of the tower.
Answer:
573.6 ft
Step-by-step explanation:
The mnemonic SOH CAH TOA reminds you of the relationship of right triangle sides and angles:
Tan = Opposite/Adjacent
This tells us ...
tan(61°) = (height)/(distance to first point)
or
distance to first point = height/tan(61°)
Likewise, ...
distance to second point = height/tan(32°)
Then the difference of the distances is ...
distance to second point - distance to first point
= height/tan(32°) -height/tan(61°)
600 ft = height × (1/tan(32°) -1/tan(61°))
Dividing by the coefficient of height, we have ...
height = (600 ft)/(1/tan(32°) -1/tan(61°)) ≈ (600 ft)/(1.04603) ≈ 573.6 ft
Answer:
574
Step-by-step explanation: